INCREASING STUDENTS’ VOCABULARY USING LITERATURE: CLASSROOM ACTION RESEARCH AT SMA NEGERI 1 PAITON - Fuadah, Mar’ah Zamratin; Tirmidi, Tirmidi; Jumaatik, Jumaatik (Jurnal Review Pendidikan dan Pengajaran, 2025)
This study aims to improve the vocabulary of grade XI Soshum-2 students at SMA Negeri 1 Paiton through a literature-based learning approach. This study uses the classroom action research (CAR) method, based on the Kemmis and McTaggart model, which consists of four cycles: planning, action, observation, and reflection. The research subjects were 23 students in class XI Soshum-2 with data collection instruments in the form of vocabulary tests, classroom observations, and documentation. In this cycle, the literature-based learning strategy was implemented through English songs, resulting in an increase in the average vocabulary score from 77,17 to 94,78. The percentage of students who achieved the minimum passing grade (KKM) was 60,87%. The observation results showed an increase in student motivation and engagement in learning. This study concludes that literature-based learning is effective in improving students' vocabulary, and it recommends integrating it continuously into the English curriculum.